Positioning care as "being with the other" within a cross-cultural context: Opportunities and challenges of pastoral care provision amongst people from diverse cultures - Magezi, Vhumani (Verbum et ecclesia, 2020)
Pastoral care is an intervention that relies on good and quality relationships between the caregiver and the cared individual, if effective and positive outcomes are to be realised. With increased intermixing of people due to migration, globalisation and other technological advances, caregivers find themselves in complex and awkward situations when attempting to ‘care for other’ persons from different cultural contexts. This challenge presents opportunities for developing and strengthening innovative care. On the other hand, the challenge poses a threat of worsening the situation or failure to positively alter it. Within this context, the critical humane factor of “being with the other person”, enshrined in African humane thinking, as indicated by the notion of Ubuntu, provides a lens of "doing" care across cultures. Care, humaneness and being with the other people are notions that bind humanity universally and yet their expression differs across cultures. This article proposes a framework for positioning pastoral caregiving within a global context as well as suggests guidelines on how global pastoral care utilising the notion of "being with the other" in global context can be done. Intradisciplinary and/or interdisciplinary implications: The article explores the notion of pastoral care from the perspective of care within the global context of pastoral ministry. It draws from the African concept of Ubuntu to develop a care approach that is humane and relational in an effort to foster relevant care across different contexts. The study has direct implications for practical theology particularly pastoral care within cross cultural missions and anthropology.